ISU KEAGAMAAN DALAM PEMBINGKAIAN MEDIA (ANALISIS FRAMING BERITA POLEMIK JILBAB DI SMK NEGERI 2 PADANG PADA DETIK.COM DAN REPUBLIKA ONLINE) - Rahmat Rio Yuherdi; Ernita Arif; Sarmiati Sarmiati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study discusses the media framing of the coverage of the hijab polemic at SMK Negeri 2 Padang. The media studied were Detik.com and Republika Online. This study uses a qualitative method, with a framing analysis approach. By using Robert N. Entman's framing analysis model, which consists of four elements of the framing device, namely Define Problems (defining the problem), Diagnose Causes (estimating the cause of the problem), Make Moral Judgment (Making Moral Choices) and Treatment Recommendations (emphasizing the solution), the results of this study shows that Detik.com frames the polemic coverage of the hijab case at SMKN 2 Padang, by giving the frame that this case is a form of intolerance, is a form of forcing the use of the hijab for non-Muslim students, is not in accordance with the values of Pancasila and is a form of violation on Human Rights (HAM). The intolerant frame is the dominant frame developed. Meanwhile, Republika Online provides a frame of misinterpretation, miscommunication, a form of respect for local wisdom, there is no element of coercion, the issue of the hijab regulation at SMKN 2 Padang is exaggerated and there is no intimidation, regarding the polemic coverage of the hijab case for non-Muslim students at SMKN 2 Padang.Keywords: Media, framing, hijab, SMK Negeri 2 Padang, West Sumatra.